Implementasi Program Corporate Social Responsibility (CSR) dan Dampaknya Terhadap Kinerja Keuangan PT.Buana Sanjaya di Papua Barat - Fadiyah Meilani; Nur Sandi Marsuni (Jurnal Ilmu Manajemen Profitability, 2019)
This study aims to find out the implementation and accountability that has been done by the company towards the community in the company environment so that it can contribute directly to the community and profit profits for companies that affect the impact of the financial performance of PT. Buana Sanjaya in West Papua. Data collection techniques used in this study are interviews and observations. This type of research is quantitative descriptive using a sampling technique that is purposive sampling. Data samples were obtained from the company's annual report from 2013 to 2017. The data obtained were analyzed using statistics, namely using simple regression. The results of this study indicate that the implementation of corporate social responsibility (CSR) programs has a positive and significant effect on financial performance at PT. Buana Sanjaya in West Papua. This can be seen from the linear regression equation as follows: KEU = -0.849 + 4.604 CSR with a significance value t = 0.011 0.05 and the determinant coefficient (R2) 0.913 or 91.3%.